2015
DOI: 10.1007/s40808-015-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil crack morphology analysis using image processing techniques

Abstract: The present paper demonstrated an image processing technique of surface soil crack analysis. The geometric features of cracks, such as width, length, and surface area are estimated. These parameters are important, because they influence both the soil hydraulics and mechanics. The crack intensity factor was introduced as a descriptor of the extent of surficial cracking. The correlation analysis indicates that area-weighted mean ratio of soil-crack area to perimeter and index r has a much closed positive relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Factors such as the slope of the terrain (23.8%) and rainfall coupled with runoff (25.7%) emerge as primary natural causes, highlighting their substantial impact on soil stability. Similar factors were identified in studies conducted by Belay and Mengistu (2019); Leta and Megersa (2021), while Shit et al (2015) confirmed that heavy rainfall and steep slopes were the primary and secondary causes of soil erosion, respectively. Moreover, the scarcity of land for farming and settlements stands out as a significant factor contributing to the ongoing deforestation in the Sebeya drainage area (IWRM, 2017).…”
Section: Analysis Of Review Questionnaire 1 What Are the Tangible Ind...supporting
confidence: 79%
“…Factors such as the slope of the terrain (23.8%) and rainfall coupled with runoff (25.7%) emerge as primary natural causes, highlighting their substantial impact on soil stability. Similar factors were identified in studies conducted by Belay and Mengistu (2019); Leta and Megersa (2021), while Shit et al (2015) confirmed that heavy rainfall and steep slopes were the primary and secondary causes of soil erosion, respectively. Moreover, the scarcity of land for farming and settlements stands out as a significant factor contributing to the ongoing deforestation in the Sebeya drainage area (IWRM, 2017).…”
Section: Analysis Of Review Questionnaire 1 What Are the Tangible Ind...supporting
confidence: 79%
“…Since crack morphology has inspired many studies, the image analysis technique has been crucial in monitoring the cracking process of soils in laboratory experiments using tools based on X-ray tomographic images [28] and photographic images [29][30][31][32][33], and several indices have been proposed based on the measurements. For example, the crack intensity factor (CIF) is defined as the ratio of the crack area to the initial area [15].…”
Section: Quantification Of Soil Crackingmentioning
confidence: 99%
“…The study utilizes desiccation crack parameters which are the soil crack intensity (Dc) and soil crack index (r) and was computed to characterize the desiccation cracking of the untreated and treated soil specimens [13]. The intensity of soil crack and cracking index are the parameters to describe the soil cracking process, and they are expressed using the linear surface areas of the formula specified in Eqs.…”
Section: Soil Crack Intensity and Index Parametermentioning
confidence: 99%
“…Mistakes can be reduced with the digital image analysis method, and reliable, realistic data can be obtained. The image analysis technique is currently utilized by various studies to characterize desiccation cracking study of untreated and treated expansive soils quantitatively [13]. First, color images of the cracked samples are converted into calibrated greyscale images and later changed into binary black-and-white photos.…”
Section: Soil Crack Intensity and Index Parametermentioning
confidence: 99%